LEGISLASI HUKUM ISLAM DI INDONESIA (Sejarah Dan Relevansi Praktis Pembaharuan Hukum Nasional) - Rosman, Edi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
This paper portray the importance of the legislative process and the history of the development and renewal of Islamic law in Indonesia. The importance of legislation is because Islamic law in the form of Shariah and fiqh can not be implemented due to various factor. One factor that makes it difficult to be implemented is the dominance of the diversity of Fiqh Mahzab as well as another factors. In its historical records, some already implemented in the Religious Court, within certain limits. Religious Courts will not fully implement shari'ah and fiqh if its not regulated in the form of laws as written law. Islamic law Maslahah that has been enacted will engender multi maslahah. To reduce the diversity of mazhab fiqh, not only with the judicial process, but also with the process of legislation that will create legal unification,legal certainty and its emplementation can be enforced through state institutions. Social change will be realized if the Islamic law enacted relevant to social needs.